Immunolocalisation of the serotonin in the fundus ventriculi and duodenum of the Asia minor ground squirrel (Spermophilus xanthoprymnus) - Timurkaan, Sema; Ozkan, Ender; Ilgun, Ramazan; Gur, Fatih Mehmet (Univ Zagreb Vet Faculty, 2009)
The endocrine cells of the proximal duodenum and fundus ventriculi of the citellus (Spermophilus xanthoprymnus) were investigated using the immunohistochemical method. Serotonin immunoreactive cells were located and distributed in the fundus and duodenum with variable frequencies. They were spherical or spindle-shaped and the highest frequency serotonin immunoreactive cells were detected in the whole fundic region. The regional distribution of the endocrine cells in the fundus and duodenum of the citellus resembled other mammalian species.
Keywords: immunohistochemistry; serotonin; endocrine cells; gastrointestinal tract; Asia minor ground squirrel